Research in the sociology of organizations. Vol. 17 (Emerald, 2000)
A work on organizational politics that is part of a series that considers the theoretical, methodological and research issues relevant to organizational sociology. It emphasizes micro and macro sociological approaches.
Keywords: Organizational sociology -- Research.; Organizational behavior.; elektronické knihy; electronic books